Healing potential of nanocarriers containing essential oils: a literature review - Barin, Ruth; Machado, Alencar Kolinski; da Silva, Ivana Zanella; Ourique, Aline Ferreira (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Essential oils are compounds of natural origin with numerous therapeutic properties, however, there are limitations regarding their stability, being easily degraded by processes of oxidation, volatilization, heating and light, characteristics that can be overcame with the use of nanotechnology. The aim of this study was to investigate the main types of nanocarriers used to carry essential oils and to assess their healing potential. A research was carried out in the Web of Science database, without a time limit, using the Boolean descriptors and markers: nano* AND essential oils AND wound healing. Articles published in Portuguese and English, with free access to the full article on the online platform, were included in the review. The research resulted in 168 articles, of which 22 were selected to include this review according to the proposed criteria. From the studies included in this review, it was possible to observe that nanocarriers such as nanoemulsions and nanofibers were able to activate the functionality of essential oils effectively and safely, achieving success in healing and antibacterial activity, demonstrating that nanotechnology is a promising alternative to develop nanotechnology-based formulations containing essential oils for wound healing.